Intraskeletal Osteohistovariability Reveals Complex Growth Strategies in a Late Cretaceous Enantiornithine - Atterholt, Jessie; Poust, Ashley W.; Erickson, Gregory M.; O’Connor, Jingmai K. (Frontiers in Earth Science, 2021)
Most crown-birds experience rapid growth, reaching adult size within a year. Rapid growth strategies evolved within Aves multiple times during the Cretaceous, documented in the Confuciusornithiformes and the Ornithuromorpha. In contrast, osteohistological data suggest the Enantiornithes, the dominant clade of Cretaceous terrestrial birds, were characterized by much slower growth rates that were sustained longer into adulthood. Here we provide evidence for a unique growth strategy involving relatively rapid growth in the Late Cretaceous avisaurid enantiornithine, Mirarce eatoni. Multiple appendicular skeletal elements were sectioned for osteohistological analysis. These show remarkable intraskeletal variation, and high levels of variation even between individual sections. The radius is composed of parallel-fibered bone, similar to histological descriptions in other enantiornithines. Other elements, in contrast, differ markedly from other members of the clade. The humerus is composed of parallel-fibered bone with a middle layer of incipient fibrolamellar bone and several growth lines in the outer circumferential layer and near the endosteal border. The endosteal and periosteal layers of slow-growing bone indicate cyclical variation in growth rates. The femur shows regions of coarse compact cancellous bone and parallel-fibered bone with numerous secondary osteons, and only a single growth line. The tarsometatarsus is predominantly fibrolamellar in texture, with several asymmetrical growth lines located throughout the cortex; this element exhibits strong cortical drift. Growth lines in both the endosteal and periosteal portions of the cortex indicate that, like the humerus, growth rates of this bone varied cyclically. The two phalanges studied here are composed of parallel-fibered bone with extensive evidence of and remodeling over possible regions of coarse compact cancellous bone. Although Mirarce is one of the largest known enantiornithines, slow and protracted growth documented in similarly-sized taxa suggests this bone texture is not merely a size-related scaling effect. These findings indicate that by the Late Cretaceous, some enantiornithines had evolved absolutely higher growth rates and more complex life history strategies, in which growth rates varied across the skeleton. Furthermore, a variety of strategies were employed to achieve adult size and morphology, including cycles of slow and fast growth, asymmetrical growth within a single element, and extensive remodeling.